Kinh nghiệm xây dựng chuẩn đầu ra chương trình đào tạo giáo dục đại học - Đặng Thị Thanh Thủy, Đặng Thị Thanh Thủy; Nguyễn Ngân Hà, Nguyễn Ngân Hà; Hoàng Thị Thảo, Hoàng Thị Thảo (Tạp chí Giáo dục, 2026)
In the context of international educational integration, ensuring and enhancing the quality of higher education has become an urgent requirement. This study focuses on analyzing the role and process of developing outcome-based curriculum (OBC) as a strategic solution to meet the quality accreditation standards of academic programs. The analysis identifies four main stages in the process of developing an outcome-based curriculum: (1) defining the program objectives and learning outcomes based on societal needs and the National Qualifications Framework; (2) designing the program structure and course syllabi based on a learning outcome alignment matrix; (3) selecting and implementing teaching, learning, and assessment methods according to the principle of Constructive Alignment; and (4) conducting regular program improvement through data analysis and stakeholder feedback. The findings also reveal several potential challenges in the implementation process, including limited faculty awareness, lack of coordination and collaboration, and resource constraints. Correspondingly, a number of practical suggestions are proposed. The study also proposes recommendations and affirms that the development of training programs based on training programs is the core driving force for higher education institutions to innovate and improve the quality of training.